Optimizing Cost and Performance in Online Service Provider Networks - Zhang, Zheng; Zhang, Ming; Greenberg, Albert; Hu, Y. Charlie; Mahajan, Ratul; Christian, Blaine (NSDI, 2010)
We present a method to jointly optimize the cost and the performance of delivering trafﬁc from an online service provider (OSP) network to its users. Our method, called Entact, is based on two key techniques. First, it uses a novel route-injection mechanism to measure the performance of alternative paths that are not being currently used, without disturbing current trafﬁc. Second, based on the cost, performance, trafﬁc, and link capacity information, it computes the optimal cost vs. performance curve for the OSP. Each point on the curve represents a potential operating point for the OSP such that no other operating point offers a simultaneous improvement in cost and performance. The OSP can then pick the operating point that represents the desired trade-off (e.g., the “sweet spot”). We evaluate the beneﬁt and overhead of Entact using trace-driven evaluation in a large OSP with 11 geographically distributed data centers. We ﬁnd that by using Entact this OSP can reduce its trafﬁc cost by 40% without any increase in path latency and with acceptably low overheads.